Essential sources in the scientific study of consciousness - Baars, Bernard J.; Banks, William P.; Newman, James B. (Bradford book., 2003)
Consciousness is at the very core of the human condition. Yet only in recent decades has it become a major focus in the brain and behavioral sciences. Scientists now know that consciousness involves many levels of brain functioning, from brainstem to cortex. The almost seventy articles in this book reflect the breadth and depth of this burgeoning field. The many topics covered include consciousness in vision and inner speech, immediate memory and attention, waking, dreaming, coma, the effects of brain damage, fringe consciousness, hypnosis, and dissociation. Underlying all the selections are the questions, What difference does consciousness make? What are its properties? What role does it play in the nervous system? How do conscious brain functions differ from unconscious ones? The focus of the book is on scientific evidence and theory. The editors have also chosen introductory articles by leading scientists to allow a wide variety of new readers to gain insight into the field.